2023
DOI: 10.1063/5.0142386
|View full text |Cite
|
Sign up to set email alerts
|

The impact of nodes of information dissemination on epidemic spreading in dynamic multiplex networks

Abstract: Epidemic spreading processes on dynamic multiplex networks provide a more accurate description of natural spreading processes than those on single layered networks. To describe the influence of different individuals in the awareness layer on epidemic spreading, we propose a two-layer network-based epidemic spreading model, including some individuals who neglect the epidemic, and we explore how individuals with different properties in the awareness layer will affect the spread of epidemics. The two-layer networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…This type of information prompts individuals to take self-protection measures, such as social distancing and vaccinations, thereby exerting a significant influence on disease transmission. [25][26][27][28][29][30][31] Researchers have increasingly focused on the relationship between information and disease, and have achieved gratifying results. For instance, Funk et al investigated the influence of information on dynamic disease transmission, revealing that information can regulate the magnitude of infectious disease outbreak.…”
Section: Introductionmentioning
confidence: 99%
“…This type of information prompts individuals to take self-protection measures, such as social distancing and vaccinations, thereby exerting a significant influence on disease transmission. [25][26][27][28][29][30][31] Researchers have increasingly focused on the relationship between information and disease, and have achieved gratifying results. For instance, Funk et al investigated the influence of information on dynamic disease transmission, revealing that information can regulate the magnitude of infectious disease outbreak.…”
Section: Introductionmentioning
confidence: 99%
“…Infectious diseases can be transmitted between people, animals and goods which always threaten human survival and take great challenges to whole world [ 1 3 ]. In recent decades, a large number of mathematical models for infectious diseases have been built and studied widely to realize the infectious disease.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that these two kinds of information have contrary impacts on epidemic prevention and control. Additionally, Feng et al [ 28 ] uncovered how individuals with different properties in the information diffusion layer influences the transmission of epidemics. These investigations suggest that epidemic spreading is highly related to the relevant information diffusion.…”
Section: Introductionmentioning
confidence: 99%